(untitled) (Sains Humanika, 2013)
Dialogue template (DT) is a fluency tool, conceptualized based on chunking and template theories to aid limited English proficiency (LEP) learners in their fluency practice. This article shares findings of learners’ gain scores on their speech rate (SR) and average length of pause (ALP) after a month of instructional intervention. Qualitative analyses found teacher’s observation and participants’ responses converged in three aspects of DT efficacy: SR improvement, chunks-assisted practice and sense of confidence. Findings are discussed in relation to its practical implications in the classroom as well as beyond the study, particularly on chunks analysis, pausing phenomena and alternative fluency tool.